Combating pirated optical disc in federal territory Kuala Lumpur under the enforcement provision of the copyright act 1987 / Shamsul Nizam Khalil, Basaruddin Mohiyuddin and Mohd Shahran Mohd Arshad - Khalil, Shamsul Nizam; Mohiyuddin, Basaruddin; Mohd Arshad, Mohd Shahran (2012)
As the pirated disc activities in Federal Territory Kuala Lumpur are still rampant, it causes a big impact on the government, enforcement agency and consumers. It is librarybased research, how ever, semi-structured interviews were also carried out which lead to a few finding of this study. The main act that governs the optical disc product is the copyright 1987 (Act 322). Besides Act 322, the manufacturing of optical disc product also governed under the Optical Disc Act 2000 (Act 332). The Trade Description (Optical Disc Label) Order 2010 is to regulated safety feature using distinct hologram label for optical disc product in Malaysia are clearly identified. Certain provisions in The Copyright Act 1987 need to be reviewed to accommodate with the current situation. It is recommended stiffer penalty be imposed and power of arrest should be given under The Optical Disc Act 2000 and Trade Description (Optical Disc Label) Order 2010. The study examines and compares the enforcement agency in Kuala Lumpur City Hall (DBKL). There are some areas in terms of man power and laws that could be improves and adopted from other enforcement agency.